Efektivitas dan kontribusi retribusi izin mendirikan bangunan terhadap retribusi daerah - Nurul Afifah; Ilham; Asma Ulhusna (PT Bone Jaya Kreatif, 2022)
The purpose of this study was to determine and analyze the effectiveness of the building permit levy on the Maros Regency regional levy and the contribution of the building permit levy to the 2017-2020 regional levy. The method used to answer the problems in this research is descriptive quantitative. The results of the analysis of this study indicate that the effectiveness of receiving building permits for retribution for the Maros Regency regional levy in 2017 is quite effective, The effectiveness of receiving the building permit levy on the Maros Regency regional levy in 2018 is very effective, The effectiveness of receiving the building permit levy on the Maros Regency regional retribution 2019 is very effective, and the effectiveness of receiving building permits levies on Maros Regency regional levies in 2020 is very effective. The contribution of building permit levy receipts to Maros Regency regional levies in 2017 has moderate criteria, the contribution of building permit retribution receipts to Maros Regency regional levies in 2018 is moderate, the contribution of building construction permit retribution receipts to Maros Regency regional levies in 2019 is quite good, and contributions The acceptance of the building permit levy on the Maros Regency regional levy in 2020 is quite good.